Developing ethnomathematics-based digital quizzes with gamification on the blooket platform - Ratnah Kurniati MA; Michael Inuhan; John Nandito Lekitoo; Fenty Madelin Madubun; Arche Febry Bonara; Jafrandi Jonsen Reiwuty; Novania Sawo (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
This study describes the development of an ethnomathematics-based digital quiz combined with a cultural context that was developed by applying the 4D methods of instruction (Define, Design, Develop, Disseminate). Focusing on the concept of number patterns, the quiz integrates local cultural elements from 3T regions such as weaving motifs, ceremonial structures, and traditional rituals to enhance relevance and engagement. The quiz items were designed to suit the Blooket platform, emphasizing short narratives, age-appropriate cognitive levels, and engaging gamification features that promote active learning. Validation results confirmed that the quiz items were content-valid, instructionally effective, and practical for classroom use. Limited trials demonstrated that the media significantly increased student motivation and engagement, particularly when mathematical concepts were presented through culturally familiar formats. Feedback from teachers and students indicated that the quiz holds promise as an inclusive and adaptive formative assessment tool, responsive to the realities of education in remote areas. The study recommends expanding the media to include a broader range of mathematical topics and cultural representations from across Indonesia. Integration with complementary learning resources such as thematic modules or game-based activity sheets, may further enhance its function as both an evaluation tool and a medium for independent, enjoyable learning. To ensure successful implementation, targeted teacher training in gamification strategies is essential, especially in schools with limited digital access.